Antrolith in the Maxillary Sinus; Report of a Case - A. Haraji; N. Mohtasham; MR. Zareh; H. Pezeshkirad (Tehran University of Medical Sciences, 2006)
A case of maxillary antrolith in a 14-year-old girl is presented. A radiopaque mass, thought to be a supernumerary tooth, was incidentally found on a panoramic radiograph obtained for orthodontic purposes. During surgical exploration the maxillary sinus was penetrated and 6 calcified masses were discovered. Histopathologic analysis revealed a calcium deposition around a necrotic mass.